UPAYA MENINGKATKAN KEAKTIFAN SISWA KELAS 3B DALAM PEMBELAJARAN PJOK MELALUI LKPD BERBASIS AKTIVITAS DI SDN 2 LOKTABAT SELATAN - Rizky, Muhammad; Rahmadi; Fakhruddin; Sujarwoko; Arifin, Fani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low level of student activeness in Physical Education, Sports, and Health (PJOK) learning on the topic of Healthy and Balanced Nutrition in Class III B of SDN 2 Loktabat Selatan. The study aimed to improve student activeness through the implementation of Activity-Based Student Worksheets (LKPD). This research employed Classroom Action Research (CAR) conducted collaboratively in two cycles. The research subjects were 29 students of Class III B at SDN 2 Loktabat Selatan. Data were collected through observation and documentation and analyzed using descriptive comparative analysis by comparing the results of the pre-cycle, Cycle I, and Cycle II. The results showed a significant improvement in student activeness. In the pre-cycle, the average student activeness score was 26,60%, categorized as low. After the implementation of Activity-Based LKPD in Cycle I, the score increased to 61.58%, categorized as moderate. In Cycle II, the average score further increased to 92.04%, categorized as high and exceeding the success indicator of 80%. The findings indicate that the implementation of Activity-Based LKPD successfully improved the activeness of Class III B students in PJOK learning on the topic of Healthy and Balanced Nutrition at SDN 2 Loktabat Selatan.